Comparative analysis of techno-economic and techno-environmental approach to optimal sizing and dispatch of hybrid solar–battery systems - Luka Smajila; Silvia Trevisan; Farzin Golzar; Ketan Vaidya; Rafael Guedez (Energy Conversion and Management: X)
This study investigates the techno-economic and techno-environmental performance of photovoltaic (PV) solar systems coupled with battery energy storage systems (BESS) in a Swedish context. The research uses mixed-integer linear programming (MILP) to optimise the dispatch strategy, minimising both operational costs and CO2eq emissions. By analysing grid signals, including electricity price and carbon intensity, the study determines the optimal size and operation of PV-BESS. The base case in Sweden was further examined by comparing the system with Italy and Poland, and by testing it with different load demand profiles. Italy and Poland were chosen due to their higher variability in grid price and carbon footprint, respectively, as well as more favourable solar conditions. The industrial and industrial shift profiles were chosen to assess the impact of load profiles with less variability compared to the base case residential profile. The key findings reveal distinct differences between economic and environmental optimisation, impacting system performance and highlighting the need for a balanced approach. Local conditions, such as grid signal volatility and solar PV production, are shown to significantly influence optimal system configurations. In Sweden, the economic approach led to higher system utilisation due to greater price volatility, while the environmental approach prioritised lower emissions. Additionally, the trade-offs between economic and environmental optimisation can lead to cost/environmental footprint increases between 25% and up to several times higher (up to 300 %). The study also finds that reducing the levelised cost of energy (LCOE) or levelised carbon footprint (LCO2eq) from the investor perspective may not always translate into significant end-user benefits. This further highlights the importance of including various stakeholder perspectives in the analysis, especially in the context of decision support. Sensitivity analysis indicates that oversizing the PV system leads to a rapid increase in costs and emissions. The addition of BESS can justify this increase by scaling the Renewable Energy Self-Sufficiency (RESS) value. Furthermore, there are diminishing returns for oversizing the battery. This research is relevant for various stakeholders, including project developers, policymakers, and researchers involved in renewable energy integration. Future research could further refine optimisation strategies for PV-BESS systems by delving deeper into specific aspects such as grid signal analysis and diverse end-of-life (EoL) pathways.